2012
DOI: 10.1002/cite.201100242
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Considerations on Thermophilic Digestion of Maize Silage at Different Feeding Modes

Abstract: Digestion of maize silage in batch, semi‐batch and continuous mode was investigated under similar experimental conditions with the aim to compare the degradation kinetics. The modeling with the 1st order equation shows that despite the ensiling pre‐treatment the disintegration/hydrolysis step determines the total degradation rate of the substrate. The results confirmed an extremely high adaptation capability of anaerobic biocenosis to increased feeding frequency, rather than to higher but less frequent loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The lower utilization of the co-substrate could probably be corrected by increasing the hydraulic retention time and giving the process more time to fully use the relatively recalcitrant meadow grass. This indicated that meadow grass was a suitable co-substrate for the AD process and that the anaerobic microbial communities of the reactor were already adapted to the substrate . The average methane yields of P-I and P-II (Figure a) had no significant differences ( p > 0.05).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The lower utilization of the co-substrate could probably be corrected by increasing the hydraulic retention time and giving the process more time to fully use the relatively recalcitrant meadow grass. This indicated that meadow grass was a suitable co-substrate for the AD process and that the anaerobic microbial communities of the reactor were already adapted to the substrate . The average methane yields of P-I and P-II (Figure a) had no significant differences ( p > 0.05).…”
Section: Resultsmentioning
confidence: 92%
“…This indicated that meadow grass was a suitable co-substrate for the AD process and that the anaerobic microbial communities of the reactor were already adapted to the substrate. 35 The average methane yields of P-I and P-II (Figure 4a) had no significant differences (p > 0.05). During period P-III, another steady state was established (days 75−91), with an average methane production rate of 765 ± 31 NmL of CH 4 L −1 day −1 (73% of the expected methane production with 64.0 ± 0.2% CH 4 in the biogas), which was 31% higher (p < 0.05) compared to the methane production rate at period P-II.…”
Section: Energy and Fuelsmentioning
confidence: 88%
“…1 (ADM1) is the multifaceted model, which represents great complexity and includes an excessive number of parameters [9]. Such a complexity increases the precision of the model, but conversely produces practical complications as all the required data is not often collected [10].…”
mentioning
confidence: 99%